2017
DOI: 10.1002/jcp.26197
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of regulation of the ITGA6 and ITGB4 genes by RUNX1 in myeloid cells

Abstract: Integrins are transmembrane adhesion receptors that play an important role in hematopoiesis by facilitating interactions between hematopoietic cells and extracellular matrix components of the bone marrow and hematopoietic tissues. These interactions are important in regulating the function, proliferation, and differentiation of hematopoietic cells, as well as their homing and mobilization in the bone marrow. Not surprisingly altered expression and function of integrins plays a key role in the development and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The transcription factors, C-MYC and ZKSCAN3 have been reported to directly bind to ITGB4 promoter and regulate ITGB4 transcription in colorectal cancer 11, 27. And the interaction of ITGB4 promoter with some transcription factors in other disease is also reported, such as KLF4 in glioma 21, RUNX1 in myeloid leukemia 22, ZEB1 in prostate cancer 23, TP73 in lung cancer 24, GLI1 in ovarian cancer 25, and JUN in pancreatic cancer 26. Ferraro et al .…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factors, C-MYC and ZKSCAN3 have been reported to directly bind to ITGB4 promoter and regulate ITGB4 transcription in colorectal cancer 11, 27. And the interaction of ITGB4 promoter with some transcription factors in other disease is also reported, such as KLF4 in glioma 21, RUNX1 in myeloid leukemia 22, ZEB1 in prostate cancer 23, TP73 in lung cancer 24, GLI1 in ovarian cancer 25, and JUN in pancreatic cancer 26. Ferraro et al .…”
Section: Discussionmentioning
confidence: 99%
“…ITGA6 has been shown to be regulated at multiple layers. Many transcription factors, including RUNX1, HIFs and FOSL1, bind to the ITGA6 promoter and enhance its transcription [27,51,52], while KLF9 represses the transcription of ITGA6 by binding its promoter region [53]. More recently, a study showed that MYC can directly control ITGA6 promoter activity in CRC cells, leading to overexpression of the pro-proliferative ITGA6A splice variant [54].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin β4 subunit expression appears to be mainly regulated at the transcript level but the mechanism of its overexpression in CRC cells is still incompletely understood. There have been a number of studies that have reported specific potential interactions of transcription factors with the ITGB4 promoter since its cloning [27] in a variety of cell types including RUNX1 [28], JUN [29] and KLF4 [30]. In CRC cells, MYC was the first transcription factor identified that promotes ITGB4 transcription [25] but recent studies have found others such as ZKSCAN3 [31] and FOSL1 [32] that need to be considered.…”
Section: Regulation Of Expressionmentioning
confidence: 99%